The value of formal planning for strategic decisions: A comment - Foster, Mandie (Strategic Management Journal, 1986)
Abstract In an earlier paper in the SMJ , Armstrong (1982) conducted a review of the empirical evidence relating to the question of whether formal planning for strategic decision‐making pays off, or more concisely whether strategic planning pays. Armstrong found that the evidence was equivocal. He also found that the methodological purity of a number of the 12 studies, which he claimed to constitute the totality of the evidence, was in doubt. For that reason he assessed the rigour of the studies relative to a framework previously proposed by Terpstra (1981). Using this framework he found that the studies rated poorly.